Rancangan Sistem Informasi IT Helpdesk berbasis Web Pada PT. Nusa Raya Cipta Tbk. - Junadi, Bambang (STMIK Banjarbaru, 2024)
The use of information technology has a major impact on data processing processes including data processing of the company PT. Nusa Raya Cipta Tbk. PT. Nusa Raya Cipta Tbk. Is a construction services company located at Jln. DI Panjaitan No.40 East Jakarta. In addition to providing great benefits, the use of information technology in companies also raises problems from the use of information technology where these problems can be caused by user ignorance or imperfections in software or hardware and other technical problems, when users have problems, users report them to the IT department and are still done manually, namely by visiting the IT department and reporting it or via WhatsApp. This study also uses a descriptive approach. The IT helddesk information system designed by researchers uses the Waterfall Method. The design of this IT helddesk information system makes it easy for users to make reports of their problems and see the progress of their reports and makes it easier for the IT department to solve user problems. Keywords: Information System; Information technology; IT Helddesk; Waterfall AbstrakPenggunaan teknologi informasi memiliki dampak yang besar terhadap proses pengolahan data termasuk pengolahan data perusahaan PT. Nusa Raya Cipta Tbk. PT. Nusa Raya Cipta Tbk. Adalah perusahaan jasa kontruksi yang berlokasi di Jln. DI Panjaitan No.40 Jakarta Timur. Selain memberi keuntungan yang besar penggunaan teknologi informasi pada perusahaan juga memunculkan masalah dari penggunaan teknologi informasi dimana masalah tersebut bisa disebabkan karena ketidak tahuan pengguna maupun ketidak sempurnaan software maupun hardware serta masalah tehnis lainnya, ketika pengguna mempunyai masalah pengguna melaporkannya ke bagian IT dan dilakukan masih secara manual yaitu mendatangi bagian IT dan melaporkannya atau melalui WhatsApp. Penelitian ini juga menggunakan pendekatan deskriptif. Sistem informasi IT helpdesk yang dirancang peneliti menggunakan Metode waterfall Rancangan sistim informasi IT heldesk ini memudahkan pengguna dalam membuat laporan permasalahannya dan melihat kemajuan laporannya dan memudahkan bagian IT menyelesaikan permasalahan pengguna.